Social protection index: Trend and regional pattern of a multidimensional index in Iran - Habibullah Hosseinpour Aghaei; Mehdi Basakha; Seyed Hossein Mohaqeqi Kamal (Social Sciences and Humanities Open)
Social protection can reduce the gap in the living conditions of individuals. Social protection interventions are usually implemented through providing the social insurances, social assistances and labor market programs. However, there is still a little consensus on its measurement. This study sought to construct a composite social protection index (SPI) in Iran and unfold its pattern among Iran's provinces during the period 2011 to 2020. The confirmatory factor analysis validated the model and confirmed the reliability and validity of the composite index. According to the results, the Iran's SPI decreased from 47.97 in 2011 to 47.71 in 2020. Additionally, the social insurance sub-index was found to be more concentrated among the central provinces, whereas social assistance was provided to a greater extent in the peripheral provinces. According to Iran's Comprehensive Welfare and Social Security Law, social insurance is the primary pillar of the country's social protection system. However, it appears that social assistance is currently the main form of social protection intervention.